2016
DOI: 10.3233/bmr-160696
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin D deficiency trigger carpal tunnel syndrome?

Abstract: The present findings demonstrated that CTS may be triggered by vitamin D deficiency, and that the severity of CTS was correlated with vitamin D levels in the deficiency group. Additionally, there was a correlation between weight gain and neuropathic pain intensity in CTS patients with vitamin D deficiency. The present findings indicate that vitamin D levels should be assessed in CTS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
5
12
0
2
Order By: Relevance
“…The present study showed that CTS patients had a significantly low vitamin D levels than controls. This observation was in agreement with recent studies (Tanik et al 2016 ). Similarly, in their study, Gursoy et al ( 2016 ) observed significantly low vitamin D level in patients with CTS compared to controls.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present study showed that CTS patients had a significantly low vitamin D levels than controls. This observation was in agreement with recent studies (Tanik et al 2016 ). Similarly, in their study, Gursoy et al ( 2016 ) observed significantly low vitamin D level in patients with CTS compared to controls.…”
Section: Discussionsupporting
confidence: 94%
“…As we classified the CTS patients according to the electrophysiologic severity into mild, moderate, severe groups, the lowest vitamin D levels were observed in patients with severe CTS. Tanik et al ( 2016 ) demonstrated that the severity of vitamin D deficiency was associated with CTS severity which was matching with our results. Different from ours, Gursoy et al ( 2016 ), who studied patients with CTS and classified them into electrophysiologically confirmed and electrophysiologically negative groups, found no significant relation between severity of CTS and vitamin D levels in their cohort.…”
Section: Discussionsupporting
confidence: 93%
“…TNF and macrophage-microglia, which cause sensitization of the peripheral and central nervous system and inhibit the stimulating mechanism 22 . Donato and colleagues emphasized that vitamin D plays a role in anti-VEGF agent and it may be the first line treatment because it is cheap and effective in the treatment of CTS 4 .…”
Section: Discussionmentioning
confidence: 99%
“…There are very scarce data on the role of vitamin D in neuropathic pain. One observational study has shown possible associations between vitamin D deficiency and carpal tunnel syndrome [ 17 ], and an interventional study showed positive effect on diabetic neuropathy after a very high single-dose of vitamin D [ 18 ]. However, in this review we will focus on the role of vitamin D in nociceptive and inflammatory pain.…”
Section: Definitions Of Painmentioning
confidence: 99%